Indonesian Pre-service Teacher Journey in International Teaching Practicum - Barlaman, Moh. Aang Fajar; Umamah, Atik (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
The increasing importance of cross-cultural competence in education has made international teaching practicum (ITP) programs essential for pre-service teachers. These programs provide unique opportunities to enhance pedagogical skills and develop global awareness, particularly for English as a Foreign Language (EFL) teachers in diverse cultural contexts. However, the specific experiences of Indonesian pre-service teachers participating in ITP programs remain underexplored. This study aims to explore the experiences of Indonesian pre-service English teachers during an ITP program in Malaysia, focusing on the journey, personal growth, and professional development achieved throughout the program. Using a qualitative narrative inquiry approach, this exploratory case study examined the experiences of one Pre-service teacher from the English Education Department, referred to as "Budi," in a Malaysian pesantren. Data were collected through semi-structured interviews, reflective journals, and program documentation, then analyzed thematically using Braun & Clarke (2006) framework. The findings reveal that the participant gained essential teaching skills, leadership qualities, and cross-cultural understanding while facing challenges such as time management, cultural adaptation, and limited teaching opportunities. These experiences contributed significantly to the participant’s personal and professional growth, highlighting the transformative impact of ITP programs. The study underscores the importance of ITP programs in preparing globally competent educators. By documenting the lived experiences of a pre-service teacher, the research provides valuable insights for program designers and policymakers seeking to enhance the effectiveness of international teaching initiatives.